Effect of natural light deficiency induction in some fenological stages of wheat - Wendt, Wilmar; Caetano, Vanderlei (Pesquisa Agropecuaria Brasileira, 2014)
During the winter growing season in the state al Rio Grande do Sul, Brazil, it is very common to occur cloudy days. Low light intensity brings about reduction in the dry weight content of plants and consequently the grain yield is also affected. With the objective of verifying the influence of light intensity in some stages of development of wheat plants, an experiment was conducted in the Centro Nacional de Pesquisa de Trigo of EMBRAPA. To cut down the light intensity to 60% of natural light, a device called "sombrite" was used to simulate the shading effect. When the plants reached the stages of a) principal stem plus two tillers; b) booting, and c) anthesis, they were shaded with the "sombrite" for one to four weeks. Beginning to count from the first week, samples of plants were collected, and the content of dry matter was evaluated under the condition of low light intensity (with sombrite) and under normal condition (without sombrite). It was concluded that under low light intensity (shading effect) from the first week on, reduction of dry matter of wheat was detected. This reduction was noticed independently of the fenologic stage of wheat. Furthermore, it was observed that a reduction in the emission of new tillers occurred mainly at the final stage of vegetative development.